Re-imagining Professional Experience in Initial Teacher Education Narratives of Learning - Fitzgerald, Ange; Parr, Graham; Williams, Judy (Springer Nature Singapore : Imprint: Springer, 2018)
XII, 213 p. 3 illus. in color.